Impact of digital trade policy on regional carbon efficiency: a quasi-experimental study in China - Lin Ni; Huwei Wen; Xiaoyan Ding (Scientific Reports)
Abstract Digital trade brings opportunities for the region to develop an open economy, and also leads to changes in regional green productivity and progress towards carbon neutrality. This study uses pilot policies of cross-border e-commerce cities as a quasi-experiment to examine how digital trade policies affect regional carbon emission efficiency. It is found that the carbon efficiency of the pilot cities was significantly improved after the intervention policy of digital trade. This conclusion is still supported by the entropy balance matching sample and the estimator after considering the heterogeneity treatment effect. Digital trade policies can help developing countries improve sustainable competitiveness and pursue carbon neutrality. In addition, digital trade can significantly promote regional energy productivity and green production technology, which is conducive to the improvement of carbon emission efficiency. These findings provide implications and insights for making low-carbon development policies in the era of digital trade.